ANALISIS YURIDIS TINDAK PIDANA PENCURIAN DENGAN KEKERASAN DI KABUPATEN PINRANG - Aswat, Hazarul (PETITUM, 2014)
The study aims to determine the application of criminal law material to the crime of theft with violence Pinrang, and how the consideration of the judge ruled against the crime of theft. This study took place in the District Court and State Attorney Pinrang. Interview data collection methods directly to the officials of the two institutions. Other documents which are files District Court Pinrang hereinafter writer qualitative analysis. From the results of this study the authors analyzed the application of the criminal law is not the right material because the defendant can be proven legally and convincingly or meet formulation offenses charged. Likewise consideration is not appropriate because the judge based on the facts revealed in the judicial proceedings.